The global financial cycle, bank capital flows and monetary policy. Evidence from Norway - Ragna Alstadheim; Christine Blandhol (Norges Bank, 2018)
We investigate the importance of a global financial cycle for gross capital inflows based on monthly balance sheet data for Norwegian banks. The VIX index has been interpreted as an "investor fear gauge" and associated with a global financial cycle. This index has also been found to impact real activity. We include both a global activity variable and the VIX index in our structural VAR model of capital inflows. We find that when global activity falls, banks' foreign funding share falls. Our results suggest that global real activity rather than a global financial cycle is a main driver behind the volume of bank capital inflows. We also study domestic monetary policy and implications for capital flows. Domestic monetary policy helps absorb VIX shocks and there is no indication of procyclical ("carry trade") effects on funding. Monetary policy affects activity and inflation in a standard fashion, and the exchange rate acts as a buffer when shocks hit the economy.
hdl:11250/2500928
Keywords: 330; structural VAR; uncertainty-shocks; bank capital flows; E32; E44; F32; F62; G15